EFEKTIVITAS PEMBELAJARAN KOOPERATIF TIPE COURSE RIVIEW HORAY TERHADAP HASIL BELAJAR MATERI PENCEMARAN LINGKUNGAN DI SMPN. 1 PULAURAKYAT ASAHAN - Qonita Aini Pane (Universitas Negeri Medan, 2016)
The researchers aimed to determine the effect of the use of cooperative learning model Course ReviewHoray the learning outcomes of students of class VII SMP. 1 Pulaurakyat learning year 2015/2016. The studypopulation numbered 245 students. Of the 245 students, defined sample of 35 students were taken randomly(random sampling). The method used in this research is the experimental method. The instrument used to collectdata is a multiple choice test. Hypothesis testing is done by using the t test. Data obtained showed that the abilityof student learning outcomes before using cooperative learning model Course Review Horay fall into the categorywith a value less than the average (mean) were obtained by the students is 60.71, while the ability of studentlearning outcomes after using cooperative learning model type course review horay fall into both categories withthe average value (mean) were obtained by the students was 77.42. Thus rejected and accepted, which means thatthere is the influence of cooperative learning model Course Riview horay on learning outcomes of students of classVII SMP. 1 Pulaurakyat learning year 2015/2016. This suggests that the results of the science lesson after usingcooperative learning model Course Riview horay better than learning outcomes before the model pembelajarncooperative Course Riview horay, and the learning process after using cooperative learning model Course Riviewhoray berefektif positively to student learning outcomes in learning science.Keywords: Effectiveness, Course Riview Horay